2018
DOI: 10.1098/rstb.2017.0043
|View full text |Cite
|
Sign up to set email alerts
|

An emergentist perspective on the origin of number sense

Abstract: The finding that human infants and many other animal species are sensitive to numerical quantity has been widely interpreted as evidence for evolved, biologically determined numerical capacities across unrelated species, thereby supporting a ‘nativist’ stance on the origin of number sense. Here, we tackle this issue within the ‘emergentist’ perspective provided by artificial neural network models, and we build on computer simulations to discuss two different approaches to think about the innateness of number s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 103 publications
3
59
0
Order By: Relevance
“…In conclusion, we believe that a deeper understanding of numerosity perception will require considering alternatives to the search for evidence of adherence to idealized, essential characteristics: We should also strive to define what could be the underlying mechanisms giving rise to the complex behavioral patterns observed in these studies. Promising results in this direction have been recently achieved by connectionist modelingfor example, by showing how approximate adherence to Weber's law can emerge in generic neural networks that learn the statistics of their visual environment (Stoianov & Zorzi, 2012;Zorzi & Testolin, 2018), or how developmental trajectories of numerical acuity in children can be simulated by progressive deep learning (Testolin, Zou, & McClelland, 2020). Further research is required to explore these issues more fully, keeping in mind that we must be prudent when characterizing the actual patterns observed in the empirical data.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we believe that a deeper understanding of numerosity perception will require considering alternatives to the search for evidence of adherence to idealized, essential characteristics: We should also strive to define what could be the underlying mechanisms giving rise to the complex behavioral patterns observed in these studies. Promising results in this direction have been recently achieved by connectionist modelingfor example, by showing how approximate adherence to Weber's law can emerge in generic neural networks that learn the statistics of their visual environment (Stoianov & Zorzi, 2012;Zorzi & Testolin, 2018), or how developmental trajectories of numerical acuity in children can be simulated by progressive deep learning (Testolin, Zou, & McClelland, 2020). Further research is required to explore these issues more fully, keeping in mind that we must be prudent when characterizing the actual patterns observed in the empirical data.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that deep belief networks can indeed simulate basic numerical abilities 39 . However, in the original model only cumulative area was taken into account as possible confound, and subsequent simulations presented anectodical evidence that stronger congruency manipulations can affect model's responses 40 . Here we push this modeling approach one step further.…”
mentioning
confidence: 98%
“…Is there a set of fundamental properties underlying the structure and dynamics of deep neural networks?Some insights into these challenging questions have been gained by inspecting deep learning systems with methods borrowed from neuroscience. For example, response profiles of individual neurons in deep networks often exhibit an impressive match with neurophysiological data [31,54,56,61]. Similarly, at the neuronal population level it has been shown that the representational space developed by deep networks has a striking overlap with that observed in the inferior temporal cortex of the primate brain [15,26].…”
mentioning
confidence: 99%